PENGEMBANGANKARAKTERTOKOHUTAMAPELAKUBULLYING TERHADAPTOKOHINDIVIDUTULIDALAMANIMEKOENO KATACHI(聲の形) - Fauzi, Aldi; Rahardjo, Turnomo; Suryanto Gono, Joyo Nur (Interaksi Online, 2024)
he anime Koe no Katachi is a character development movie themed, where the protagonist, Ishida Shouya, changes into a better personality after he bullies the deaf individual character, Nishimiya Shouko. This research aims to see how Ishida Shouya's character development process is depicted in the Koe no Katachi anime and find out the movie strategy/logic used in developing the protagonist's character. This type of research is descriptive qualitative with a narrative analysis method using the concept of The Positive Change Arc from K.M. Weiland to see the stages of Ishida Shouya's character development. Petrie & Boggs Character Identification Theory is used to analyze the character through the viewpoint of conflict and characterization. The results show that the movie uses three main strategies in developing its protagonist's character: (1) Bringing down the protagonist from a stable position, (2) Bringing up the character's redemption efforts after experiencing the fall, and (3) Bringing up the character's acceptance of reality. Researchers found some shortcomings: (1) Simplification of Karma in the Narrative, (2) Ignoring the Potential for Collective Recovery, and (3) Risk of Glorifying the Redemption of the Main Character. Nevertheless, overall, the Koe no Katachi anime successfully depicts an individual's journey of redemption through a complex and in-depth narrative.